Transparent ZnO thin film deposition by a compact planar magnetron device - Villamayor, Michelle Marie S. (Animo Repository, 2014)
A 120 mm diameter by 80 mm compact planar DC magnetron device capable of maintaining a pure H2O discharge was used to deposit conducting transparent ZnO thin film on glass substrates via plasma enhanced chemical vapor deposition (PECVD). A square Zn target with an area of 55 ' 55 mm2 placed at the cathode was sputtered by argon-oxygen plasma at 100 mA discharge current and %550 to %680 V discharge potential. Gaseous H2O was introduced into the system as a source of reactive oxygen at 600 mPa in addition to argon fed at 100 mPa. For the deposition duration of 3, 5, and 7 min, the thickness measured was 21.5, 15, and 16 nm, respectively. The interface between the glass and oxide layer was dependent on the deposition duration— smooth for the 3-min deposition and rough for the 5 and 7 min durations. FTIR and UV–vis spectrometries show % transmittance in UV to IR range is inversely proportional to deposition time. The thin films exhibited electrical conductance. © 2014 The Japan Society of Applied Physics